(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study, titled (manifestations of bureaucracy in Iraq’s educational institution) seeks to identify the mechanism of administrative work of the bureaucratic organization in the educational institution, and how it manages the work in terms of its orientations and the extent of its efficiency and quality in the completion of administrative work in the institution. The study found the following: 1- Government institutions, especially our educational institutions, need to reconsider the organization of institutional work and end cases of mediation and nepotism within educational institutions. 2- Working on selecting leaders within the institution on the basis of efficiency, quality and academic qualifications. As for the study’s recommendations, theseinclude: 1- The necessity of working to run awareness sessions for workers in higher education and scientific research institutions, each according to his/her specialization, academic qualifications and field of work. 2- The need to redouble efforts by administrative leaders in institutions of higher education and scientific research in order to reform the work of the ministry and its affiliated institutions.